Preservation of Pancasila Cultural Values by Millennials in The Development of Trends in Globalization Era - Renata Noorawhita (Universitas PGRI Adi Buana Surabaya, 2021)
Backgrounds: The current stronger current of globalization has created many trends among the millennial generation. Most of the current trends are trends with the